Research on the Application of Artificial Intelligence for Human Resource Management through Knowledge Resources - Om Kumar Harsh; Akhilesh Harsh (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This theoretical study defines the potential applications of Artificial Intelligence (AI), explicit and tacit knowledge and the respective knowledge reuse for the development of human resource environments. It primarily examines the influence and specific features of Artificial Intelligence (AI), providing an essential understanding of its role in modern organizational contexts. It then analyses the influence of Artificial Intelligence (AI) on improving human resource environments by examining explicit, tacit knowledge, and their reuse. The study then analyses the main bottlenecks and limitations that hinder the optimal integration of Artificial Intelligence (AI)into organizational management practices. Finally, it highlights the Main Advantages of Artificial Intelligence (AI) in human resources strategic development. It has been noted that the management of explicit and tacit knowledge and their reuse benefits establishments or organizations. They result in increased efficiency, including reduced task repetition, followed by improved performance of new employees. These studies adopted a conceptual or theoretical approach and presented an innovative concept for integrating tacit, explicit, and reusable knowledge.